2018
DOI: 10.25115/ejrep.v16i44.1939
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relation between alexithymia in parents and children? Effects on children’s quality of life

Abstract: Introducción. El estudio de la alexitimia en niños (especialmente en niños sanos), a diferencia de la población adulta, no ha sido estudiado ampliamente, a pesar de su estrecha relación con la salud y la calidad de vida. El objetivo de este estudio fue analizar por un lado, la relación entre la alexitimia infantil y la alexitimia de sus padres, y por otro lado, la relación entre la alexitimia infantil y la calidad de vida de los niños, así como establecer si esta relación está mediada por la alexitimia de los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In line with this report, results of Rieff and Di Trani have shown that alexithymia is correlated with internalizing behaviors such as obsession, depression, anxiety, and negative thoughts such as worry and rumination in children ( 38 , 45 ). Personality traits such as controlling behaviors in parents are correlated with development of alexithymia, especially with emotional expression and difficulty in identifying feelings ( 46 ). It seems that children’s alexithymia, with consequences such as isolation and not being able to identify others’ feelings, play a mediating role in the connection between mother’s personality and the degree of internalization in children ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this report, results of Rieff and Di Trani have shown that alexithymia is correlated with internalizing behaviors such as obsession, depression, anxiety, and negative thoughts such as worry and rumination in children ( 38 , 45 ). Personality traits such as controlling behaviors in parents are correlated with development of alexithymia, especially with emotional expression and difficulty in identifying feelings ( 46 ). It seems that children’s alexithymia, with consequences such as isolation and not being able to identify others’ feelings, play a mediating role in the connection between mother’s personality and the degree of internalization in children ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors hold that alexithymia can also be transmitted intergenerationally [ 43 ], which is explained in light of the difficulties alexithymic parents face in socializing emotions [ 48 ]. In some research investigating samples of different ages, parental alexithymia correlated with that of children [ 49 , 50 , 51 ]. However, not all results confirm this hypothesis [ 29 , 52 ], or studies confirm it only partially for some age groups [ 53 ].…”
Section: Introductionmentioning
confidence: 99%